AAV9 intracerebroventricular gene therapy improves lifespan, locomotor function and pathology in a mouse model of Niemann–Pick type C1 disease. (5th June 2018) - Hughes, Michael P; Smith, Dave A; Morris, Lauren; Fletcher, Claire; Colaco, Alexandria; Huebecker, Mylene; Tordo, Julie; Palomar, Nuria; Massaro, Giulia; Henckaerts, Els; Waddington, Simon N; Platt, Frances M; et al.
Abstract: Niemann– Pick type C disease (NP-C) is a fatal neurodegenerative lysosomal storage disorder. It is caused in 95% of cases by a mutation in the NPC1 gene that encodes NPC1, an integral transmembrane protein localized to the limiting membrane of the lysosome. There is no cure for NP-C but there is a disease-modifying drug (miglustat) that slows disease progression but with associated side effects. Here, we demonstrate in a well-characterized mouse model of NP-C that a single administration of AAV-mediated gene therapy to the brain can significantly extend lifespan, improve quality of life, prevent or ameliorate neurodegeneration, reduce biochemical pathology and normalize or improve various indices of motor function. Over-expression of human NPC1 does not cause adverse effects in the brain and correctly localizes to late endosomal/lysosomal compartments. Furthermore, we directly compare gene therapy to licensed miglustat. Even at a low dose, gene therapy has all the benefits of miglustat but without adverse effects. On the basis of these findings and on-going ascendency of the field, we propose intracerebroventricular gene therapy as a potential therapeutic option for clinical use in NP-C.